A cardiac implantable device infection by Raoultella planticola in an immunocompromized patient. (28th February 2017) - Adjodah, Chandra; D'Ivernois, Chistophe; Leyssene, David; Berneau, Jean-Baptiste; Hemery, Yann
Abstract : Introduction. Infection of cardiac implantable electronic devices is a severe condition associated with high mortality, particularly in patients who are dependent upon heart-pacing devices. Staphylococci are found in 70 % of reported cases. Case presentation. We report the case of a cardiac-pacemaker infection in a 79-year-old man, cumulating a history of rheumatoid arthritis treated by corticosteroids and methotrexate by a recently identified micro-organism: Raoultella planticola . He presented local signs of infection on his VVI pacemaker implantation site and underwent urgent pocket device replacement under cefamandole antibioprophylaxis. On incision thick pus oozed out. It was necessary to perform a complete hardware extraction comprising the pulse generator and the ancient lead. Pus was inoculated into aerobic and anaerobic culture vials and Gram staining unveiled Gram-negative rods. Microbiology analysis identified the organism as R. planticola. A new pacing device was inserted on the contrlateral pectoral region. Ciprofloxacin enabled full recovery. A literature review concerning this pathogen revealed that it is involved in severe infections such as bloodstream infections, peritonitis, cellulitis, pneumonia and lung abscesses, and urinary tract infections. In these case reports, underlying co-morbidities were identified such as solid active neoplasia, recent chemotherapy, corticosteroids, solid-organ-recipient patients and recent open surgery. Conclusion. R. planticola is a serious emerging pathogen and contributes to the burden of various infectious conditions. Its pathogenicity and occurrence should be known by clinicians and a high level of awareness is necessary to precisely identify it provide the correct antibiotic regimen.